The Relationship Between Stress, Safety Behaviour And Mindfulness Of Project Team Members - Tan, Zhee Cin (2022)
Working in construction industry is stressful due to its stress is one of the major contributor to harsh working characteristics workplace acci while dents and injuries as stress can negatively impact an individual’s safety behaviour. Project team members with tight deadlines and huge workloads and thus it is essential to are always deal ing develop an appropriate strategy for enhancing their a promising tool work perfor mance as well as safety and health. The benefits of mindfulness have been reported by a large body of studies and they suggested that mindfulness is for between mindfulness, s unknown. Therefore, managing stress and safety behaviour. However, the relationship tress and safety behaviour of project team members still remains to fill in this research gap, Malaysia a questionnaire survey was conducted among project team members who are working in the construction industry within Kuala Lumpur or Selangor, . To further understand the factor s affecting mindfulness, this research also examined the effect of working experience on mindfulness of project team members. The results revealed that project team members with higher mindfulness were likely to h ave lower stress and better safety behaviour. Furthermore, this research also found that working experience was positively correlated with mindfulness of project team members. These results indicated that mindfulness can be used to predict stress as well a s safety behaviour of project team members. Mindfulnessbased training programs can be effective to improve employees safety and health, leading to better work performance. ’